Perancangan Aplikasi Chatbot Pusat Informasi Mahasiswa Pada Telegram Messenger Dengan Menggunakan Fulltext Search Boolean Mode (Studi Kasus : STMIK PGRI Tangerang) - Hokianto Candra; Rino .; Riki Riki (Komunitas Dosen Indonesia, 2019)
Chatbot can be used as a solution of human resource issues in term of answering user’s questions about STMIK PGRI Tangerang. A chatbot application can have a conversation or answer user’s questions automatically. Knowledge is needed for chatbot to work properly. The general scheme of chatbot’s knowledge is the existence of patterns and responses. This research will implement the Fulltext Search Boolean Mode for the pattern-matching process with the input received by the chatbot application based on Telegram Messenger Bot. Chatbot application which created in this research can provide answers to information that is relevant to the input or questions provided by users.